2002
DOI: 10.1073/pnas.062043799
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium/methylammonium transport (Amt) proteins facilitate diffusion of NH 3 bidirectionally

Abstract: The ammonium͞methylammonium transport (Amt) proteins of enteric bacteria and their homologues, the methylammonium͞ ammonium permeases of Saccharomyces cerevisiae, are required for fast growth at very low concentrations of the uncharged species NH3. For example, they are essential at low ammonium (NH4 ؉ ؉ NH3) concentrations under acidic conditions. Based on growth studies in batch culture, the Amt protein of Salmonella typhimurium (AmtB) cannot concentrate either NH3 or NH4 ؉ and this organism appears to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 20 publications
7
88
2
Order By: Relevance
“…A possible explanation of this observation is an energyindependent transport by ammonium channels, which facilitates diffusion, rather than by permeases, which concentrate ammonium inside the cell by an energydependent transport mechanism. This kind of transport mechanism was first suggested by Soupene and coworkers for ammonium transporter AmtB from Salmonella typhimurium [32,33] and was further supported by the recently published structure of E. coli AmtB [17] as well as by transport data [14].…”
Section: Discussionsupporting
confidence: 52%
“…A possible explanation of this observation is an energyindependent transport by ammonium channels, which facilitates diffusion, rather than by permeases, which concentrate ammonium inside the cell by an energydependent transport mechanism. This kind of transport mechanism was first suggested by Soupene and coworkers for ammonium transporter AmtB from Salmonella typhimurium [32,33] and was further supported by the recently published structure of E. coli AmtB [17] as well as by transport data [14].…”
Section: Discussionsupporting
confidence: 52%
“…Based on the predominantly nonpolar nature of the pore of AmtB, both structural studies have concluded that conduction of the charged form appears energetically highly unfavorable and that NH 3 must be the permeating species as suggested by the Kustu group for some time [37,39]. Stopped-flow experiments with purified AmtB reconstituted into proteoliposomes [19] and a recent in vivo functional characterization of E. coli AmtB are also consistent with this view [18].…”
Section: Protein Mediated Ammonia Conductionsupporting
confidence: 56%
“…In contrast to the prevailing view of interpreting cellular methylammonium accumulation as Amt/MEP-mediated secondary transport as reviewed by von Wire´n and Merrick [42], Kustu and collaborators [37,39,40] have attributed this accumulation to metabolic trapping by glutamine synthetase or to trapping in acidic vacuoles in the case of fungi. They proposed instead that Amt/MEP proteins simply mediate bi-directional NH 3 transport and this view is now strongly supported by the structural results.…”
Section: Amt /Mep-mediated Ammonia Uptake For Nutritionmentioning
confidence: 69%
“…From experimental evidence suggesting that AmtB and Mep proteins facilitate diffusion of NH 3 across the cytoplasmic membrane of bacteria and fungi respectively [40,41], Soupene and co-workers have also speculated that mammalian Rh proteins might be gas channels. However, based on the relatively restricted organ and tissue distribution of Rh proteins and the observation that mutants of Chlamydomonas reinhardtii lacking the paralogue Rh1 protein grow very slowly under high CO 2 conditions, these authors further suggested that mammalian Rh proteins might function as CO 2 rather than as NH 3 gas channels [42,43].…”
Section: Discussionmentioning
confidence: 99%